Evaluation of Lipid Profile changes in children with urinary tract infections - Ammar Lateef Hussein (Tikrit Journal of Pure Science)
Back ground:  many researches about  urinary tract infection has been conducted on adults but very little has been done on children. Therefore, this research is novel in Salahaddin city-Iraq.